Perilaku Makan Pada Individu Obesitas Dengan DM Tipe 2 Selama Pandemi Covid-19 Di Wilayah Kerja Puskesmas Sidorejo Lor, Kota Salatiga - Nugroho, Kristiawan Prasetyo Agung; Triandhini, R. L. N. K. Retno; Widita, Desia Siwi (Universitas Tribhuwana Tunggadewi, 2023)
Obesity is one of the risk factors for diabetes mellitus. Obese people have a higher risk of insulin resistance. The emergence of the COVID-19 pandemic prompted the Indonesian government to enforce policies ranging from large-scale social restriction and transition to implementing emergency community activity restrictions at levels 1–4 that can have impacts that affect people’s lives, including affecting diets. The study aims to find out the dietary picture of adult obese individuals with type 2 diabetes mellitus in the work area of Puskesmas Sidorejo Lor, Salatiga City, during the COVID-19 pandemic. The study respondents were individuals aged 25–59 years of age, with a total of 22 people identified with type 2 diabetes mellitus and obesity. The research uses quantitative descriptive methods with instruments such as Semi-quantitative Food Frequency questionnaires and Food recalls. Data is analyzed using the Food Ingredient Composition List, Nutrisurvey, and Microsoft Excel. The results of the study showed that the respondents’ energy, protein, and fat consumption was excessive, while the average respondent’s carbohydrate intake had a severe deficit. The study concluded that there was an imbalance in respondent intake because respondents reduced their consumption of carbohydrates, especially white rice, but their protein and fat intake was not in line with their needs.